Human Umbilical Cord Mesenchymal Stem Cells to Treat Neuromyelitis Optica Spectrum Disorder (hUC–MSC–NMOSD): A Study Protocol for a Prospective, Multicenter, Randomized, Placebo-Controlled Clinical Trial - Yao, Xiao-Ying; Xie, Li; Cai, Yu; Zhang, Ying; Deng, Ye; Gao, Mei-Chun; Wang, Yi-Shu; Xu, Hui-Ming; Ding, Jie; Wu, Yi-Fan; Zhao, Nan; Wang, Ze; et al. (Frontiers in Neurology, 2022)
Background：Neuromyelitis optica spectrum disorder (NMOSD) is a severe relapsing and disabling autoimmune disease of the central nervous system. Its optimal first line treatment to reduce relapse rate and ameliorate neurological disability remains unclear. We will conduct a prospective, multicenter, randomized, placebo-controlled clinical trial to study the safety and effectiveness of human umbilical cord mesenchymal stem cells (hUC-MSCs) in treating NMOSD. Methods：The trial is planned to recruit 430 AQP4-IgG seropositive NMOSD patients. It consists of three consecutive stages. The first stage will be carried out in the leading center only and aims to evaluate the safety of hUC-MSCs. Patients will be treated with three different doses of hUC-MSCs: 1, 2 or 5×106 MSC/kg·weight for the low, medium and high dose group respectively. The second and third stage will be carried out in six centers. The second stage aims to find the optimal dosage. Patients will be 1:1:1:1 randomized into the low, medium, high dose group and the controlled group. The third stage aims to evaluate the effectiveness. Patients will be 1:1 randomized into the optimal dose and the controlled group. Primary endpoint is the first recurrent time and secondary endpoints are the recurrent times, EDSS scores, MRI lesion numbers, OSIS scores, Hauser walking index and SF-36 scores. Endpoint events and side effects will be evaluated every 3 months for 2 years. Discussion：Although hUC-MSC has shown promising treatment effect of NMOSD in preclinical study, there is still a lack of well-designed clinical trials to evaluate the safety and effectiveness of hUC-MSC among NMOSD patients. As far as we know, this trial will be the first one to systematically demonstrate the clinical safety and efficacy of hUC-MSC in treating NMOSD and might be able to determine the optimal dose of hUC-MSC for NMOSD patients. Trial registration：The study was registered with Chinese Clinical Trial Registry (CHICTR.org.cn) on Mar 2, 2016 (registration No. ChiCTR-INR-16008037), and the revised trial protocol (Protocol version 1.2.1) was released on March 16, 2020.